Biological anthropology the natural history of humankind - Stanford, Craig B. (Craig Britton) 1956-; Allen, John S. (John Scott) 1961-; Antón, Susan C. (Pearson Education Center, 2013)
This textbook presents a survey of physical anthropology, the branch of anthropology that studies the physical development of the human species. It plays an important part in the study of human origins and in the analysis andidentification of human remains for legal purposes. It draws upon human body measurements, human genetics, and the study of human bones and includes the study of human brain evolution, and of culture as neurological adaptationto environment. The authors use the progressive term "biological anthropology" to mean "an integrative combination of information from the fossil record and the human skeleton, genetics of individuals and of populations,our primate relatives, human adaptation, and human behavior."